Plastics and the environment - Andrady, Anthony L., ....- (New Jersey : Wiley, 2003)
PART 1.An Environmental Primer (A. Andrady).Common Plastics Materials (A. Andrady).Polymers and Energy (I. Boustead)PART 2.Plastics in Packaging (S. Selke)Plastics in Agriculture (I. Hussain & H. Hamid).Coatings (L. Hill).Wastes From Textiles Processing (B. Smith).PART 3.Environmental Effects on Polymeric Materials (N. Searle).Biodegradable Polymers (S. McCarthy).Plastics in the Marine Environment (M. Gregory and A. Andrady).Flammability of Polymers (A. Tewarson).Biodegradable Water-Soluble Polymers (G. Swift).PART 4.Polymers, Polymer Recycling, and Sustainability (J. Brandrup).Plastics Recycling (M. Fisher).Thermal Destruction of Wastes and Plastics (A. Gupta & D. Lilley).Recycling of Carpet and Textile Fibers (Y. Wang, et al.).Polymers in Automobile Applications (W. Lange).Index.
Keywords: Milieuaspecten; Plastics; Polymeren; Recyclage